1988
DOI: 10.1021/bi00423a018
|View full text |Cite
|
Sign up to set email alerts
|

Binding of calcium to the calcium adenosine triphosphatase of sarcoplasmic reticulum

Abstract: The binding of Ca2+ and the resulting change in catalytic specificity that allows phosphorylation of the calcium ATPase of sarcoplasmic reticulum by ATP were examined by measuring the amount of phosphoenzyme formation from [32P]ATP, or 45Ca incorporation into vesicles, after the simultaneous addition of ATP and EGTA at different times after mixing enzyme and Ca2+ (25 degrees C, pH 7.0, 5 mM MgSO4, 0.1 M KCl). A "burst" of calcium binding in the presence of high [Ca2+] gives approximately 12% phosphorylation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…We found that the rate constant of the fluorescence rise was about 10 s Ϫ1 at 30 M free Ca 2ϩ (pCa 4.5), and this was almost the maximal value (the rates measured at 300 M and 2 mM free Ca 2ϩ were 13 and 15 s Ϫ1 , respectively). This rate was of the same order of magnitude as that for Ca 2ϩ binding to dephosphorylated native ATPase in the absence of nucleotides under similar conditions (19,20). The Ca 2ϩ dependence of the stability of the low fluorescence species was qualitatively similar after collapsing the calcium gradient by either ionophore or detergent (data not shown).…”
Section: Fig 2 the Low Fluorescence Fitc-atpase Species Formed Frommentioning
confidence: 54%
“…We found that the rate constant of the fluorescence rise was about 10 s Ϫ1 at 30 M free Ca 2ϩ (pCa 4.5), and this was almost the maximal value (the rates measured at 300 M and 2 mM free Ca 2ϩ were 13 and 15 s Ϫ1 , respectively). This rate was of the same order of magnitude as that for Ca 2ϩ binding to dephosphorylated native ATPase in the absence of nucleotides under similar conditions (19,20). The Ca 2ϩ dependence of the stability of the low fluorescence species was qualitatively similar after collapsing the calcium gradient by either ionophore or detergent (data not shown).…”
Section: Fig 2 the Low Fluorescence Fitc-atpase Species Formed Frommentioning
confidence: 54%
“…Investigation ofthe partial reactions of the pump cycle has shown that translocation of Ca2" takes place in the first part of the cycle and can be divided into three main steps, involving binding on the cis side of the membrane, occlusion within the protein, and release to the trans side or vesicle lumen (1)(2)(3)(4)(5)(6)(7). These events at the transport site are coupled to chemical changes at the active site such as the change in the reactivity of an aspartic residue to ATP, phosphorylation of the residue to an ADPsensitive form, and then a change to an ADP-insensitive phospho form (8)(9)(10).…”
mentioning
confidence: 99%
“…These intermediates are those with the Ca21 sites oriented toward the vesicle lumen (13). In the forward direction of catalysis, the block forces the enzyme to follow the uncoupled pathway, involving direct hydrolysis of the ADP-sensitive E1-P(2Ca) intermediate (step 7).…”
mentioning
confidence: 99%
“…In E1Ca 2 , Ca 2ϩ bound at site II is rapidly exchanged with the cytoplasmic Ca 2ϩ , and the Ca 2ϩ bound at the deeper site I can be released to the cytoplasm only when site II is vacant (15,(41)(42)(43)(44). Therefore, we first labeled site I with 45 Ca 2ϩ by exchanging the site II-bound 45 Ca 2ϩ with nonradioactive Ca 2ϩ (supplemental Fig.…”
Section: Time Courses Of Ep Decay and Camentioning
confidence: 99%
“…due to Ca 2ϩ exchange with site II (see supplemental Fig. S1) (42)(43)(44). Then, 45 Ca 2ϩ uptake assay in a single turnover was performed as in Fig.…”
Section: Ca 2ϩ Release From E1pca 2 In Absence Of Kmentioning
confidence: 99%